POROSITY FORMATION IN PRODUCTS INJECTED IN ALUMINUM UNDER PRESSURE: literature review - Cesar Silva, Fernando; Cadioli, Luiz Paulo (Revista Interface Tecnológica, 2023)
This article has as its theme the formation of porosity in products injected in aluminum under pressure. As is well known, aluminum casting can occur using different methods, depending on the use and applicability of the final product. In the case of pressure casting, the use is linked to the need to obtain parts with quality and high precision. Porosity is a problem that affects this type of process. The main objective of the study is to verify the processes used to minimize the formation of porosity in parts injected in aluminum under pressure and, for that, it also sought to specify the foundry processes, especially those involving aluminum. The results of this essentially bibliographical study showed that some steps must be observed to reduce porosity, such as alloy quality, temperature control, pressure control and cooling time, in order to minimize porosity in parts from the pressure casting.
Keywords: Porosity; Pressure Casting; Aluminum